The spatial origin of-5/3 spectra in grid-generated turbulence - Laizet,S; Nedic,J; Vassilicos,JC (Physics of Fluids, 2015)
A combined wind tunnel and computational study of grid-generated turbulencealong the centreline shows that the close to −5/3 power law signature of energyspectra in the frequency domain originates relatively close to the grid not only wherethe velocity derivative statistics become quite suddenly isotropic but also wherethe turbulent fluctuating velocities are very intermittent and non-Gaussian. As theinlet flow velocity increases, these power laws are increasingly well defined andincreasingly close to −5/3 over an increasing range of frequencies. However, thisrange continuously decreases with streamwise distance from the grid even though thelocal Reynolds number first increases and then decreases along the same streamwiseextent. The intermittency at the point of origin of the close to −5/3 power spectraconsists of alternations between intense vortex tube clusters with shallow broad-bandspectra and quiescent regions where the velocity fluctuations are smooth with steepenergy spectra.